Relationship Between the Risk of Postpartum Depression and Maternal and Infant Attachment Bonding - Riska Febriani; Misrawati Misrawati; Hellena Deli (Journal of Education Technology Information Social Sciences and Health, 2024)
Introduction: Childbirth has psychological, emotional and physical impacts, involving the acquisition of new roles and parenting tasks that the mother must face. These changes can result in stress for the mother, prolonged stress causes the mother to be at risk of postpartum depression. One of the impacts is the bonding attachment of mother and baby. Objective: This study aims to determine the relationship between the risk of postpartum depression and the bonding attachment of mother and baby. Research Place: Umban Sari Community Health Center Working Area. Method: This research uses the correlation method. The research sample of 83 respondents used purposive sampling technique. The bivariate analysis used was the chi-square test. Results: The results of the statistical test analysis obtained a p-value = 0.02 0.05 with an OR value = 6.8. Conclusion: There is a significant relationship between the risk of postpartum depression and bonding attachment between mother and baby. Suggestion: After giving birth, many mothers are not aware of the symptoms of depression that occur, therefore the importance of health education and depression screening programs to prevent postpartum depression.